Pengembangan Handout Bermuatan Nilai Islam Pada Materi Sistem Reproduksi Manusia Kelas XI MA - Rum, Fathurahmi F; Hamka L, Hamka L; Syamsiah, Syamsiah (Biology Teaching and Learning, 2021)
Abstract. The aim of this study was to develop a valid handout which containing Islamic values on the material of a reproduction system that is valid and to analyze teacher and student response data to handouts. This is a research and development research (R & D), which adapts the ADDIE model which consists of 5 stage : (1) Analyze; (2) Design; (3) Development; (4) Implementation; (5) Evaluation. The validity tast of teaching materials is based on the results of the assessment of 2 expert validators, while the response data of teacher and students is obtained from the assessment of teachers and student on the use of teaching materials in MAN in Makassar city with research subjects of 2 biology teachers per school and 20 students in each school. Analysis of the result of the study showed that the developed handouts were in the valid category based on the average score of 3.3. The result of the trial are limited to the responses of teacher obtained an average value of 3.7 and are in the good category. The results of trials on students responses on average a value of 3.6 is a good category. Based on the results of the study it can be concluded that the development of handouts containing Islamic values in the material of the human reproduction system class XI MA as teaching material meets valid and practical criteria.Â  Keywords: handout, Islamic values reproduction system